1964
DOI: 10.1037/h0039921
|View full text |Cite
|
Sign up to set email alerts
|

Auditory frequency discrimination and generalization following lesions of the amygdaloid area in rats.

Abstract: Rats trained in a bar-pressing situation to discriminate between either 2 tones or tone and no-tone, based upon intermittent food reinforcement in the presence of S*, displayed consistent and often severe impairment on retention performance after large bilateral lesions in the amygdaloid area. Histological analysis also implicated the putamen in these effects. Amygdaloid impairment was closely associated with increased responding under nonreinforced conditions, with no concomitant increases in responding to S"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
13
0

Year Published

1966
1966
1993
1993

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 20 publications
4
13
0
Order By: Relevance
“…deficits in caudotomized animals have utilized relatively complex learning tasks: including, delayed and alternation responding, escape and active avoidance, lever-pressing and similar operant tasks, successive discrimination and reversal learning, and different types of maze problems (Chorover & Gross, 1963;Divac, et dl., 1978;Kirkby, 1969Kirkby, , 1978Kirkby & Kimble, 1968;Kirkby & Polgar, 1974;Mikulaus & Isaacson, 1965;Sanberg, et al, 1978;Schmaltz & Isaacson, 1968;Schwartzbaum, et al, 1964). However, most of the studies showing learning.…”
mentioning
confidence: 99%
“…deficits in caudotomized animals have utilized relatively complex learning tasks: including, delayed and alternation responding, escape and active avoidance, lever-pressing and similar operant tasks, successive discrimination and reversal learning, and different types of maze problems (Chorover & Gross, 1963;Divac, et dl., 1978;Kirkby, 1969Kirkby, , 1978Kirkby & Kimble, 1968;Kirkby & Polgar, 1974;Mikulaus & Isaacson, 1965;Sanberg, et al, 1978;Schmaltz & Isaacson, 1968;Schwartzbaum, et al, 1964). However, most of the studies showing learning.…”
mentioning
confidence: 99%
“…Other frustration-related phenomena have been observed in pigeons (Staddon & Innis, 1966), rats (Amsel & Roussel, 1952), monkeys (Davenport & Thompson, 1965) and children (Ryan & Watson, 1968). Behavioural contrast has so far been reported in pigeons (Reynolds, 1961) and retardate children (O'Brien, 1968), while peak shift has been reported in the pigeon (Hanson, 1959) and in the rat (Schwartzbaum et al, 1964;Pierrel & Sherman, 1960, 1962. Landau (1968) has looked for peak shift in normal children, but failed to find it.…”
mentioning
confidence: 99%
“…* * Similarly, Wild and Blampied (1972) and Woodruff, Means, and Isaacson (1973) report that hippocampal rats are impaired both on retention and acquisition of go-no-go. On the other hand, Schwartzbaum, Thompson, and Kellicutt (1964) showed that hippocampal rats could retain a preoperatively acquired go-no-go discrimination, the only abnormality in * We have already discussed the fact that when the cue is at a remove from the lever normal animals perform less well than do hippocampals (p. 268). * * In this study the hippocampal rats did not make more S -responses than did a control group which received bilateral hippocampal injections of sodium sulphadiazine, a drug assumed not to elicit seizures.…”
Section: Go-no-go and Non-spatial Alternationmentioning
confidence: 99%
“…As regards the use of external cues, in both Schwartzbaum et al (1964) and Gaffan (1973) separate tones were used as S + and S -and normal performance was seen in both cases. In all the other studies only one cue was used, with the exception of Mering and Mukhin (1973) who also reported normal performance.…”
mentioning
confidence: 99%
See 1 more Smart Citation